2006
DOI: 10.1029/2005jd006281
|View full text |Cite
|
Sign up to set email alerts
|

A multimodel study of the twentieth‐century simulations of Sahel drought from the 1970s to 1990s

Abstract: In this paper, we evaluate the performance of 19 coupled general circulation models (CGCMs) in twentieth‐century simulations of the Sahel during the 1970s to 1990s. Correlation, regression, and cluster analyses are applied to observations and model outputs including Sahel monthly precipitation, evaporation, soil moisture, and sea surface temperature (SST). We find that only eight CGCMs (hit models) produce a reasonable Sahel drought signal, while seven CGCMs (miss models) produce excessive rainfall over the Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…Although a number of atmospheric general circulation models (AGCMs) are able to reproduce the twentieth century drying trend in West Africa and the Sahel dry conditions of the 1970-1980s and subsequent rainfall recovery using the observed SST as boundary conditions, simulated trends and drying are substantially weaker than in the observations (e.g., Giannini et al 2003;Lu and Delworth 2005;Hoerling et al 2006Hoerling et al , 2010Lau et al 2006;Caminade and Terray 2010;Martin and Thorncroft 2014). For instance, the Climate of the twentieth century international project (C20C, Scaife et al 2009) used 14 state-of-theart GCMs with observed SSTs and other relevant data to study climate variations and changes over the last century.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of atmospheric general circulation models (AGCMs) are able to reproduce the twentieth century drying trend in West Africa and the Sahel dry conditions of the 1970-1980s and subsequent rainfall recovery using the observed SST as boundary conditions, simulated trends and drying are substantially weaker than in the observations (e.g., Giannini et al 2003;Lu and Delworth 2005;Hoerling et al 2006Hoerling et al , 2010Lau et al 2006;Caminade and Terray 2010;Martin and Thorncroft 2014). For instance, the Climate of the twentieth century international project (C20C, Scaife et al 2009) used 14 state-of-theart GCMs with observed SSTs and other relevant data to study climate variations and changes over the last century.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhang et al (2013) call into question these results as there are multiple inconsistencies between the previous experiments and key aspects of observed variability within and without the North Atlantic. Hoerling et al (2006) and Lau et al (2006) analyzed historical simulations of CGCMs participating in the CMIP3. Overall, the models failed to simulate the midtwentieth-century Sahel drought and recent recovery (Hoerling et al 2010) with the correct magnitude and timing, suggesting that anthropogenic forcings played little or no role in driving the drought.…”
Section: A Role Of Sst Anomaliesmentioning
confidence: 99%
“…More research is required to systematically evaluate climate models and to exploit fully the observational data, in order to improve the WAM prediction. Thus, far, there have been very few studies evaluating GCMs' performance in simulating the WAM in multi-model experiments (Lau et al 2006;Cook and Vizy 2006;Hoerling et al 2006;Biasutti et al 2009). The West African Monsoon Modeling and Evaluation project (WAMME), a Global Energy and Water Cycle Experiment (GEWEX)/Coordinated Energy and Water Cycle Observation Project (GEWEX/CEOP) initiative in collaboration with the African Monsoon Multi-disciplinary Analysis project (AMMA, Redelsperger et al 2006), uses GCMs and regional climate models (RCMs) to evaluate the performance of current state-of-the-art climate models in simulating the WAM precipitation, onset, withdrawal, and relevant processes at diurnal, intraseasonal, interannual, and interdecadal scales, and to address issues regarding the role of land-ocean-atmosphere interaction, land-cover and land-use change, vegetation dynamics, and aerosols, particularly dust, on WAM development It also identifies common deficiencies among models in simulating the major WAM features and provides better understanding of the fundamental physical processes involved.…”
Section: Introductionmentioning
confidence: 99%
“…SSIB-1 (Xue et al 1991) None UCLA MRF AGCM (Kanamitsu et al 2002;Xue et al 2004) T62L28 (*2°, 28 vertical levels) Chou (1992), Chou and Suarez (1999), Hou et al (1996) SAS (Pan andWu 1995, Hong andPan 1996) SSIB-1 (Xue et al 1991) None References cited in Table 1 Kanamitsu et al 2002b;Xue et al 2004), the UCLA GCM (Mechoso et al 2000;Xue et al 2009), and the COLA (Center for Ocean-Land-Atmosphere Interactions, Kinter III et al 1997) GCM have similar land surface schemes. More information on the physical components of participating models, including land surface models, can be found in Table 1.…”
Section: Introductionmentioning
confidence: 99%